ความคงทนของสีและการต้านรังสียูวีของผ้าไหมย้อมชา (COLOUR FASTNESS AND UV PROTECTION OF SILK DYED WITH TEA) - มะแซ มาหามะสูไฮมี; จ้อยพจน์ ภัทราภา; ชูพูล ภาณุมาศ; ศรีสว่าง พรชัย; นวลมังสอ นพรัตน์ (วารสารมหาวิทยาลัยศรีนครินทรวิโรฒ สาขาวิทยาศาสตร์และเทคโนโลยี, 2017)
วัตถุประสงค์ของการศึกษาในครั้งนี้เพื่อย้อมผ้าไหมด้วยชาซึ่งเป็นสีย้อมตามธรรมชาติโดยใช้สารกระตุ้นคือเหล็กคลอไรด์ (FeCl3) ทำการทดสอบความคงทนของสีต่อการซัก น้ำ เหงื่อ แสง การขัดถูและการกดทับด้วยความร้อนตามมาตรฐานการทดสอบสิ่งทอ (AATCC) และได้ทำการศึกษาการต้านรังสียูวีของผ้าไหมด้วยการคำนวณค่าการต้านรังสียูวี (Ultraviolet Protection Factor, UPF) องค์ประกอบทางเคมีที่มีอยู่ในสีย้อมธรรมชาติได้วิเคราะห์คุณลักษณะด้วยเทคนิคอินฟราเรด (FT-IR Spectroscopy) ลักษณะของสีผ้าที่ย้อมด้วยชามีสีน้ำตาลในขณะเดียวกันที่ใช้สารกระตุ้นที่เป็นเหล็กคลอไรด์จะมีสีดำ ผลการทดลองความคงทนของสีย้อมผ้าไหมพบว่ามีความคงทนของสีต่อการซักและความคงทนต่อเหงื่อในระดับปานกลางถึงดีมาก ความคงทนต่อน้ำ แสงและการกดทับด้วยความร้อนอยู่ในระดับดีถึงดีมาก สำหรับความคงทนต่อการขัดถูอยู่ในระดับปานกลาง การต้านรังสียูวีอยู่ในระดับค่าการต้านรังสียูวีในระดับดีเยี่ยม สารที่สกัดได้จากชามีสารที่อยู่ในกลุ่มพอลิฟินอลิก (Polyphenolic) และแทนนิน (Tannin) ซึ่งชาก็เป็นอีกตัวเลือกหนึ่งที่สามารถใช้ในการย้อมผ้าไหมในการผลิตสีย้อมในการย้อมผ้าอีกด้วย คำสำคัญ: สีย้อมธรรมชาติ ความคงทนของสี ผ้าไหม การต้านรังสียูวี The objective of this study was dyeing of silk fabrics using tea as a natural dye with ferric chloride (FeCl3) as mordant. The color fastness to washing, water, perspiration, light, crocking and hot pressing of the dyed samples was determined according to AATCC test methods. In this study the UV-protection properties were investigated on silk fabrics. Transmittance measurements were used to calculate the ultraviolet protection factor (UPF). The chemical functional groups of the dyes that were characterized by using fourier transform infrared spectroscopy (FTIR). Silk fabric dyed with tea had a shade of brown, while those mordanted with ferric chloride of black color shade. Our results revealed that color fastness to washing and perspiration was fair to very good level, whereas the color fastness to water, light and hot pressing were mostly good to very good level. However, the crocking fastness results showed fair level. The UV protection characteristics were also excellent protection. These extracts gave polyphenolic and tannin. Therefore, it was suggested that tea dye has the potential in producing functional dyes that could be imparted into the silk dyeing natural colourant system. Keywords: Natural Dyes, Color Fastness, Silk, UV Protection.